Pnpla3/Adiponutrin Deficiency in Mice Does Not Contribute to Steatohepatitis, Fibrosis or Cholestatic Liver Injury - Robert McMahon; Thierry Claudel; Claudia Fuchs; Tatjana Stojakovic; Hubert Scharnagl; Robert Zimmermann; Guenter Haemmerle; Erin E Kershaw; Michael Trauner (International Journal of Negative Results, 2026)
A sequence variation (I148M) in the patatin-like phospholipase domain-containing protein 3 (PNPLA3) gene has been linked to metabolic dysfunction-associated steatotic liver disease (MASLD) and the progression of MASLD and other chronic liver diseases towards fibrosis and cancer. To elucidate the role of PNPLA3 in metabolic liver injury, cholestasis or liver fibrosis, we utilized Pnpla3 knockout (KO) mice and investigated the impact of PNPLA3 deficiency on the inflammatory, cholestatic, and fibrotic phenotypes induced by MCD diet, bile duct ligation (BDL), 3,5-diethoxycarbonyl-1,4-dihydrocollidin (DDC) diet and carbon tetrachloride (CCl4), respectively. Upon MCD feeding, Pnpla3 KO and WT mice lost comparable amounts of white adipose tissue and showed similar degrees of liver injury. In addition, a down-regulation of genes regulating fatty acid oxidation was observed in Pnpla3 KO mice under chow diet, while no differences between experimental groups were seen in the expression of genes regulating fatty acid import, export, oxidation and de novo lipogenesis upon MCD feeding. Liver serum enzyme levels, fibrosis or cholestatic markers and inflammatory genes were not different between Pnpla3KO and WT mice after BDL. Markers of fibrosis, inflammation and biliary damage increased at the mRNA levels in response to DDC-induced cholestatic injury, without differences between WT and KO mice. Collagen deposition and hepatic fibrotic marker expression were similarly increased in CCl4 treated WT and Pnpla3 KO mice. Serum liver enzymes also increased upon CCL4 treatment without differences between WT and KO mice. In summary absence of Pnpla3 has no impact on the development of fatty liver, inflammation, cholestatic liver and bile duct injury, or hepatic fibrosis in mice.
Keywords: PNPLA3/adiponutrin